PERLINDUNGAN HUKUM ANAK PUBLIK FIGUR SEBAGAI KORBAN EKSPLOITASI DI MEDIA SOSIAL - Garry, (Fakultas Hukum Universitas Semarang, 2024)
This research examines the protection of children as public figures on social media. Involving children in the world of work or what is known as child labor has several applicable provisions because employing children is only allowed to develop a child's interests and talents. Exploitation can occur if children are forced to work as public figures on social media. Law Number 17 of 2016 concerning child protection was created in order to provide protection for children from all actions that are detrimental to the child's growth and development. In addition the role of the government through institutions related to child protection is one of the keys to reducing the number of child exploitation. The research method used is a normative juridical type with a statutory approach, a comparative approach supported by primary, secondary and tertiary legal materials. The results of this research show that there are regulations governing the prevention of child exploitation and provisions for child labor along with the role of KPAI as a child protection institution so that these two components should be able to suppress cases of child exploitation of public figures on social media.